Parenting in youth sport from research to practice - Holt, Nicholas L.; Knight, Camilla (Routledge, Taylor & Francis Group, 2014)
"Parents and parent-figures play a pivotal role in the development of young people in reaching their full potential in sport. The psychological and practical support of parents can be as vital to young athletes as the appropriate coaching and facilities. This book brings together current research into the impact of parenting in youth sport and examines the relationships between athletes, coaches and parents.